2012
DOI: 10.1074/jbc.m112.340935
|View full text |Cite
|
Sign up to set email alerts
|

Eps8 Protein Facilitates Phagocytosis by Increasing TLR4-MyD88 Protein Interaction in Lipopolysaccharide-stimulated Macrophages

Abstract: Background: TLR4-mediated p38 MAPK and actin cytoskeleton reorganization are important for macrophage phagocytosis. Results: TLR4-induced Eps8 facilitates TLR4-MyD88 interaction, leading to the activation of p38 MAPK, actin polymerization, and the uptake of bacteria in macrophages. Conclusion: Eps8 is critical in innate immunity. Significance: This is the first report to indicate that Eps8 contributes to efficient phagocytosis in macrophages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 49 publications
(68 reference statements)
2
22
0
Order By: Relevance
“…These findings are consistent with a role of phagocytosis and pinocytosis in the uptake of these stimuli (Fig. 3D), as LPS treatment has been shown to enhance both processes (Chen et al, 2012; Peppelenbosch et al, 1999). …”
Section: Resultssupporting
confidence: 87%
“…These findings are consistent with a role of phagocytosis and pinocytosis in the uptake of these stimuli (Fig. 3D), as LPS treatment has been shown to enhance both processes (Chen et al, 2012; Peppelenbosch et al, 1999). …”
Section: Resultssupporting
confidence: 87%
“…TLR2 and TLR4 are the principal signaling receptors for bacterial cell‐wall components. In general, recognition of LPS by TLR4 increases 1) membrane ruffling; 2) adhesion; 3) mortality; and 4) uptake of bacteria 46 , 47 . TLR2 recognizes various bacterial components, including 1) peptidoglycans; 2) lipopeptide; and 3) lipoprotein 45 , 48 .…”
Section: Discussionmentioning
confidence: 99%
“…In general, recognition of LPS by TLR4 increases 1) membrane ruffling; 2) adhesion; 3) mortality; and 4) uptake of bacteria. 46,47 TLR2 recognizes various bacterial components, including 1) peptidoglycans; 2) lipopeptide; and 3) lipoprotein. 45,48 Expression level of TLR2 mRNA, but not TLR4 mRNA, was significantly higher in A. actinomycetemcomitansinfected THP-1 cells, demonstrating that TLR2 is involved in a phagocytic capacity of THP-1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Hsp90 activation is involved in the induction of inflammation and Hsp90 inhibitors are able to counteract these effects (4,9,24). 17-Dimethylaminoethylamino-17-demethoxygeldanamycin reduces inflammation in lupus (39), blocks the NF-B inflammatory cascade in immune stimulated macrophages (40) and substantially reduces necrosisinduced cytokine production and permeability increases in a model of endotoxin-induced uveitis (34).…”
Section: Discussionmentioning
confidence: 99%
“…In endothelial cells, pp60 src is activated in response to a variety of stimuli, including H 2 O 2 , estrogen, and shear stress and leads to activation of eNOS (15). Furthermore, activated pp60 src increases the nuclear translocation of c-Jun and p65 (46) via PI3K/Akt and MAPKs (19), regulates LPS-induced actin cytoskeleton rearrangement in macrophages (9), and controls NADPH oxidase activation and ROS production (45). Indeed, Severgnini et al (38) have shown both in vivo and in vitro that inhibition of the Src kinases protects against LPS-induced acute lung injury.…”
Section: Discussionmentioning
confidence: 99%